NEEDS ANALYSIS OF ENGLISH COURSE FOR CADETS AT NUSANTARA MARITIME ACADEMY BANJARMASIN - Muhammad Arinal Rahman; Elisa Rosiana; Moch Nurdin (Akademi Maritim Nusantara, 2022)
Cadets at Nusantara Maritime Academy Banjarmasin are expected to have a strong command of the English language. They will be in a better position to succeed professionally in the future if they can speak clearly and fluently in English. This research aimed to explore the educational content that ought to be taught based on a needs analysis. This research used a mixed-method approach, consisting of a questionnaire and an interview. Cadets and lecturers from the Language Center at Nusantara Maritime Academy in Banjarmasin participated in this research. According to the study's conclusions, the course's instructional materials must be written in English and include sections on administrative abilities, communication skills, and the processes for using tools aboard ships. More opportunities for the cadets to improve their speaking and pronunciation are required. To make the English lesson more enjoyable, genuine materials and forms of media entertainment, such as songs, videos, and images, should be provided as part of the course.